The effectiveness of fixation of hydroxyapatite-coated helical blade in preventing of the cut-out observed in treatment with proximal femoral nail of fractures of the femur intertrochanteric in elderly - Tosun, Haci Bayram; Uludag, Abuzer; Serbest, Sancar; Cicek, Necati; Demir, Sukru (Turkish Assoc Trauma Emergency Surgery, 2023)
BACKGROUND: This study aimed to retrospectively evaluate the effectiveness of hydroxyapatite-coated (HA-coated) implants and other caput-collum implants in preventing cut-out observed in treatment with proximal femoral nail (PFN) of intertrochanteric femur fractures in elderly patients.METHODS: A total of 98 consecutive patients (56 males and 42 females; mean age: 79.42 (61-115) years) treated with three differ-ent PFNs for intertrochanteric femoral fractures were retrospectively examined. The mean of the follow-up period was 7.87 (4-48) months. It was used a threaded lag screw in 40 patients, an HA-coated helical blade in 28 patients and a non-coated helical blade in 30 patients for PFN. The reduction quality, fracture type, and radiological outcomes among all groups were evaluated.RESULTS: Unstable type was seen in 50 (52.1%) patients according to AO Foundation/Orthopedic Trauma Association fracture classi-fication. An acceptable-good reduction quality was seen in 87 (88.8%) of all patients. The average of tip-apex distance (TAD) value was 27.61 mm, calcar-referenced TAD (CalTAD) value was 28.72 mm, caput-collum diaphyseal angle was 128,degrees Parker's anteroposterior ratio was 46.36%, and Parker's lateral ratio was 46.82%. The best suitable implant position was observed in 49 (50%) patients. Cut-out was observed in 7 (7.14%) patients, and secondary varus displacement of more than 10 degrees was observed in 12 (12.24%) patients. Correlation analysis and multivariate logistic regression analysis showed a significant difference between HA-coated and other implants in cut-out. Furthermore, implant type was the strongest predictive factor for cut-out complications in the multivariate logistic regression analysis.CONCLUSION: HA-coated implants may reduce the long-term cut-out risk due to increased osteointegration and bone ingrowth in elderly patients with intertrochanteric femoral fractures with poor bone quality. However, this alone is not enough; a suitable screw position, optimal TAD values, and excellent reduction quality are other important factors.
Yaşlılarda intertrokanterik femur kırıklarının proksimal femur çivisi ile tedavisinde gözlenen cut-out’un önlenmesinde hidroksiapatit kaplı helikal blade tespitinin etkinliği
Keywords: Caput-collum implant; cut-out; hydroxyapatite-coated; intertrochanteric femur fractures; proximal femoral nail